The burden of sympathy : how families cope with mental illness - Karp, David A. (Oxford University Press, 2002)
In this vivid and thoughtful study, David Karp chronicles the experiences of the family members of the mentally ill, and how they draw "boundaries of sympathy" to avoid being engulfed by the day-to-day suffering of a loved one. Working from sixty extensive interviews, the author reveals striking similarities in the experiences of caregivers: the feelings of shame, fear, guilt and powerlessness in the face of a socially stigmatized illness; the frustration of navigating the complex network of bureaucracies that govern the mental health system; and most of all, the difficulty negotiati